Anália Maciel: a educadora, a escola, a cidade - Teixeira Neto, Euclides (2012)
This study aims to reconstruct the story of Education of the School called Desembargador Vicente de Lemos in the city of Senador Elói de Souza in Rio Grande do Norte in Natal- Brazil. This is done considering activities that were realized by the teacher Anália Maciel. Since the worl deals with an investigation that is related to Cultural History field, the research emphasized the school as well as the presence of female teachers, in particular Anália Maciel. Concepts present in the work of Chartier (1990), Burke (1992), Le Goff (1992) and Morais (2002) were used in order to comprehend the transformation process in which local schools have been through. This is also done considering the state educational actions of behalf of the teacher. The documental fonts regarded available records such as Governmental correspondence, Law and Decrees. The information fonts used were available at the The Geographical and Historical Institute of Rio Grande do Norte as well as the State s Public Archive. Other information fonts were newspapers such as A República, Diário de Natal and Tribuna do Norte. Some people that were contemporary with the teacher and were there when the school was created were interviewed. Discourses from the decades of 1930 and 1940 were analyzed. The research was guided by the History of Education and Scholar Institution field of analysis. The research also allows to reflect on the pedagogical practices of the time and permits to understand a past-still present -as well as all the development of process that the education went through in the historical context of the city of Senador Elói de Souza. It was also possible to acknowledge that the creation of the school represented thoroughly a landmark in the education in this city and it contributed in a determinant manner for the formation of the students